1998
DOI: 10.1056/nejm199801083380202
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Coagulation Factor VII Gene and the Risk of Myocardial Infarction

Abstract: Our findings suggest that certain polymorphisms of the factor VII gene may influence the risk of myocardial infarction. It is possible that this effect may be mediated by alterations in factor VII levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
159
5
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(182 citation statements)
references
References 23 publications
15
159
5
3
Order By: Relevance
“…Plasma CRP level, which is also a CV risk factor (Ridker, 1997), did not change either with diet or wine intervention. Plasma levels of ®brinogen and, probably those of factors VIIc and VIIIc, have direct association with CV disease (Ridker, 1997;Mead et al, 1986;Held et al, 2000;Rumley et al, 1999;Iacoviello et al, 1998;Redondo et al, 1999). It has been hypothesized that differences in diet and wine intake could partially explain the lower CV morbidity and mortality in southern European countries in comparison with their northern counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma CRP level, which is also a CV risk factor (Ridker, 1997), did not change either with diet or wine intervention. Plasma levels of ®brinogen and, probably those of factors VIIc and VIIIc, have direct association with CV disease (Ridker, 1997;Mead et al, 1986;Held et al, 2000;Rumley et al, 1999;Iacoviello et al, 1998;Redondo et al, 1999). It has been hypothesized that differences in diet and wine intake could partially explain the lower CV morbidity and mortality in southern European countries in comparison with their northern counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…77,78 Similar to fibrinogen, the latter is a known determinant of hypercoagulability and of the risk of CVD. 21,23,79 Whether a similar gradient for fibrinogen is also present also is unclear.…”
Section: Areas Of Future Researchmentioning
confidence: 99%
“…In summary, we found that about 40% of Italians carry B-MYB polymorphisms that confer a significant (Iacoviello et al, 1998). The remaining 130 control DNAs were gathered in different Italian hospitals from over 65 years noncancer patients.…”
Section: Functional Characterization Of B-myb Polymorphisms R Schwab mentioning
confidence: 89%